Which food date label brings us the most excellent opportunity to reduce food waste? Evidence from a quasi-natural intervention experiment in urban China - Shujun Cheng; Yang Lu; Yanjun Ren; Zhide Jiang; Minjuan Zhao (Agricultural and Food Economics)
Abstract Since various food date labeling (FDL) systems exist worldwide, consumers’ confusion and misunderstanding of FDL are unavoidable, which may result in a large amount of food waste at the consumer stage. To what extent consumers’ FDL cognition affects their food waste behaviors and intentions has yet been well documented. Using the online survey data (N = 7830, two-period panel) from China, we examine the relationship between FDL cognition and food waste behaviors, quantify the resulting food waste amount, and use difference-in-differences models to evaluate the net effect of the information intervention. The results show that only 6.46% of urban consumers in China have correct FDL cognition, and this cognition has a significant relationship with their food waste behaviors. The FDL information intervention significantly improves consumers’ FDL cognition and corrects their food waste intention, and the quality guaranteed date label has the most significant potential for reducing food waste, which is the most widely used FDL type in China currently. Based on the findings, strengthening the localized and targeted FDL popularization is a practical and promising way to reduce food waste, especially the most potential label type.